1988
DOI: 10.1002/mrd.1120200109
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐carbohydrate complementarity in mammalian gamete recognition

Abstract: Recent studies suggest that gamete recognition in a number of species is mediated by complementary proteins and carbohydrates on opposing gamete surfaces. Studies in invertebrates and vertebrates have shown that carbohydrate-binding proteins on the sperm surface recognize and bind to complementary glycoconjugates on the egg's extracellular coat. This chapter reviews our current knowledge of gamete recognition in the mouse. The complementary receptors for both mouse sperm and egg have been identified, purified,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
62
0
3

Year Published

1989
1989
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(67 citation statements)
references
References 88 publications
2
62
0
3
Order By: Relevance
“…It has been shown that sperm carbohydrate-binding proteins bind to glycoconjugates of the zona pellucida in different species and mediate gamete recognition (17)(18)(19). We hypothesize that ZIF-1 exerts its zona binding inhibitory activity via its carbohydrate moieties.…”
mentioning
confidence: 88%
“…It has been shown that sperm carbohydrate-binding proteins bind to glycoconjugates of the zona pellucida in different species and mediate gamete recognition (17)(18)(19). We hypothesize that ZIF-1 exerts its zona binding inhibitory activity via its carbohydrate moieties.…”
mentioning
confidence: 88%
“…It is involved in species-specific sperm-egg binding, induction of acrosome interaction, post-fertilisation block to polyspermy and embryo protection during its transit along the reproductive tract [7,26,27]. Previous biochemical studies have demonstrated that the glycan portion of the glycoproteins ZPB of the pig [29] and of ZP3 [6,24,28] of the mouse may be the complementary sperm receptors mediating the primary binding between the spermatozoon and the ZP.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, lysosomal glycosidases act to catalyze hydrolysis of the terminal glycosidically linked monosaccharide constituents of the oligosaccharide moieties of glycoproteins, glycolipids and glycosaminoglycans (for review see [1]). However, in spermatozoa, glycosidases are thought to form stable enzyme-substrate complexes by binding with high specificity and affinity to the oligosaccharide residues of the glycoproteins of the ZP without acting as a catalyzer (for review see [2]). Many investigators have found various sperm glycosidases such as α-L-fucosidase in cattle [3,4] and rats [5], α-D-mannosidase in rats [6], mice [7] and humans [8], β-D-galactosidase in rabbits [9] and rats [10][11][12] and N-acetyl-β-D-glucosaminidase (GlcNAc'ase) in sheep [13], rats [10], cattle [14], buffaloes and goats [15], mice [16] and pigs [17].…”
mentioning
confidence: 99%